2019
DOI: 10.1097/prs.0000000000005197
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Breast Reconstruction after Failed Implant-Based Reconstruction: Evaluation of Surgical and Patient-Reported Outcomes and Quality of Life

Abstract: Introduction: There is a subset of patients who initially had implant based breast reconstruction but later change to autologous reconstruction after failure of the implant reconstruction. The purpose of this study was to examine our series of patients in whom autologous reconstruction was performed after initial failed implant reconstruction, using the BREAST-Q to examine patient satisfaction and quality of life. Methods: After Institutional Review Board approval, a retrospective chart review of a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 18 publications
(28 reference statements)
3
39
0
1
Order By: Relevance
“…Prior studies have reported that in the setting of salvage free-flap breast reconstruction, complication rates may range from 7 to 21%; however, few studies have examined how complications may compare with patients who have not had a prior implant-based reconstruction. 5 6 24 Our study finds that patients with a history of implant reconstruction experienced a higher rate of major complications following free-flap reconstruction as compared with patients with no reconstructive history. This is likely related to a patient's history of radiation therapy and multiple reconstructive surgeries prior to free-flap reconstruction.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Prior studies have reported that in the setting of salvage free-flap breast reconstruction, complication rates may range from 7 to 21%; however, few studies have examined how complications may compare with patients who have not had a prior implant-based reconstruction. 5 6 24 Our study finds that patients with a history of implant reconstruction experienced a higher rate of major complications following free-flap reconstruction as compared with patients with no reconstructive history. This is likely related to a patient's history of radiation therapy and multiple reconstructive surgeries prior to free-flap reconstruction.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that free-flap breast reconstruction after failed implant reconstruction leads to improved patient outcomes. 5 6 7 More specifically, Coriddi et al compared outcomes in patients who had BREAST-Q scores available for both the implant and autologous phase of reconstruction, demonstrating that patients who underwent autologous reconstruction after failed implant reconstruction experienced significant improvement in satisfaction with their breasts, psychosocial well-being, and physical well-being. 6 However, the degree of satisfaction achieved after failed implant-based reconstruction as compared with a patient with no prior implant reconstruction remains unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, over a quarter (27.6%) of patients who initially had implant BR required a secondary reconstruction (replacement of their implant with another form of BR) over the same period. 10 The mean follow-up in this cohort was only 3.7 years, but as the median time to secondary reconstruction is between 4 11 and 6 years 12 , this may underestimate the true scale of the problem, providing further impetus for the long-term outcomes of implant-based and autologous BR to be explored.…”
Section: Introductionmentioning
confidence: 95%